Peranan School Well-Being dan Optimisme Terhadap Flow Akademik pada Mahasiswa Fakultas Psikologi Universitas “X” Padang - Ifani Candra; Hidayah, Nurul (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2023)
Being a student faces a lot of problems, both from the surrounding environment and academic problems. This study aims to determine the role of school well-being and optimism in the academic flow of students at the Faculty of Psychology, University